(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
Despite the prevalence of hierarchical structures in many organizations, rigid autocratic leadership often risks stifling the psychological dedication necessary for peak productivity. This study examined the moderating effect of employee engagement on the relationship between autocratic leadership and employee performance, specifically investigating whether engagement levels can mitigate the limitations of a leadership style. Data were gathered from 384 employees across selected institutions in Kaduna, including the Nigerian Defence Academy, St. Gerard’s Catholic Teaching Hospital, St. Anne’s Secondary School, Rapha Orthopedic Hospital, Nigerian Breweries and Barau Dikko Teaching Hospital. Utilizing a structured questionnaire, the data were analyzed via SPSS using a Hierarchical Regression Model to assess both direct effects and interaction dynamics. The findings reveal that autocratic leadership alone exerts a weak direct effect on staff performance; however, employee engagement significantly moderates this relationship. High levels of engagement were found to reduce the adverse impacts of autocratic control while concurrently enhancing performance outcomes. Based on these results, the study recommends that managers should exercise autocratic leadership selectively, restricting its application to situations requiring strict supervision, rapid decision making or high operational control, while minimizing excessive authoritarian practices that may undermine employee performance. The study further recommends that organizations should institutionalize strategies for enhancing employee engagement through effective communication, employee involvement, recognition, career development opportunities and supportive human resource policies to strengthen employee commitment and improve performance even within structured leadership environment.